The perceived risk and the high involvement product purchase: Location-based advertisements using fearful and sensual appeals as risk reduction strategy in condom purchases - Ivy E.D. Schultz (Taylor & Francis Group, 2016)
The goal of this research was to investigate the perceived risk of purchasing condoms and the risk-reducing effects of location-based advertisements. For the research, a quantitative approach was used. A questionnaire was distributed to 238 participants, using the Internet and physical distribution. This study found that 66% of the sample perceived social risk during the purchase of condoms. Of this percentage, 39% stated that embarrassment has stopped them from purchasing the product. Location-based advertisements were perceived negative, however also perceived informative by almost half of the sample. This study implies that advertisements have a positive effect on the perceived risk since the majority of the sample stated that their perceived purchase embarrassment was reduced after seeing the sensual (65%) and fearful (59%) advertisement.